Effects of endometritis treatment schemes on the subsequent reproductive efficiency of cows - KARAGIANNIDIS (Α. ΚΑΡΑΓΙΑΝΝΙΔΗΣ) A.; TSILIGIANNI (Θ. ΤΣΙΛΙΓΙΑΝΝΗ) Th.; KIPOURIDIS (Κ. ΚΗΠΟΥΡΙΔΗΣ) K.; VARSAKELI (Σ. ΒΑΡΣΑΚΕΛΗ) S.; ALEXOPOULOS (Κ. ΑΛΕΞΟΠΟΥΛΟΣ) C. (Journal of the Hellenic Veterinary Medical Society, 2018)
The effect of various treatment schemes basedon the intrauterine injection of antibacterial agents Lugol, Rifaximin, and Oxytetracycline) or a combination of these agents with PGT2a on the subsequent reproductive efficiency, was studied in 234 cows treated for endometritis after the 15th d postpartum. The main conclusions from this study were the following: a) the pregnancy rates after the fist artificial insemination (Al), as well as the repeated Als (up to 3) are neither affected by the treatment scheme nor by the time of treatment and by retreatment, b) the 1st AI, as well as conception and pregnancy are achieved a lot sooner after treatment, when there is no pre existence of retained placenta, when the treatment is applied after the 30th d postpartum, and there is no retreatment, c) intrauterine injection of Lugol gives better results, (P<0,001), as far as the «treatment to 1st AI» and the «treatment to conception» intervals is concerned (31,4±22,6 and 55,8±44,8 days respectively), in comparison to intrauterine injection of Rifaximin (46,8±23,7 and 70,1 ±41,9 days, respectively) or Oxytetracycline (60,0 ±35,3 and 92,1 ±73,0 days, respectively) and d) the combination PGF2a and intrauterine injection of antivacterial agents further reduces the «treatment to 1st AI» and the «treatment to conception» intervals (22,9 ±28,6 and 28,8 ±31,2 days, respectively, for the combination of Lugol and PGF2a, and 35,7 ±13,2 and 46,5 ±25,5 days, respectively, for the combination οι Rifaximin anaPGF2a).